2010
DOI: 10.1038/modpathol.2009.166
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear EGFR in ductal invasive breast cancer: correlation with cyclin-D1 and prognosis

Abstract: The epidermal growth factor receptor (EGFR)-family and cyclin-D1 have been extensively studied in breast cancer; however systematic studies that examine protein expression and gene status in the same cohort of patients are lacking. Also emerging evidences suggest existence of a direct EGFR-signaling pathway, which involves cellular transport of EGFR from cell membrane to the nucleus, and transcriptional regulation of the target genes. Thus, we examined the protein expression of membrane EGFR, nuclear EGFR, cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
70
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 44 publications
(70 reference statements)
7
70
0
1
Order By: Relevance
“…After overnight hybridization at 37 1C, slides were washed and CCND1/Cyclin D1 in bladder cancer counterstained with DAPI II (125 ng/ml, Vysis) in an antifading solution. A minimum of 25 non-overlapping nuclei were evaluated on each spot, and the individual spot was considered normal or amplified according to the CCND1/CEP11 fluorescence ratios o2 or Z2 18 (Figures 1a and b).…”
Section: Fluorescence In Situ Hybridization (Fish) and Immunohistochementioning
confidence: 99%
See 1 more Smart Citation
“…After overnight hybridization at 37 1C, slides were washed and CCND1/Cyclin D1 in bladder cancer counterstained with DAPI II (125 ng/ml, Vysis) in an antifading solution. A minimum of 25 non-overlapping nuclei were evaluated on each spot, and the individual spot was considered normal or amplified according to the CCND1/CEP11 fluorescence ratios o2 or Z2 18 (Figures 1a and b).…”
Section: Fluorescence In Situ Hybridization (Fish) and Immunohistochementioning
confidence: 99%
“…[14][15][16] However, amplification does not necessarily leads to protein overexpression, suggesting complex expression mechanisms. [17][18][19] In bladder cancer, information on frequency of CCND1/CyclinD1 alterations and their clinical relevance are limited. The prognostic impact has primarily been evaluated in non-muscle invasive bladder cancer for CyclinD1 and with regard to recurrence-and progression-free survival.…”
mentioning
confidence: 99%
“…21,24 Clinical studies have indicated that increased nEGFR expression is associated with poor prognosis. 25,26 The nuclear translocation of EGFR is initiated by ligandinduced endocytosis. 27 Endosome-associated EGFR is recognized by importin b in the cytoplasm and is then transported to the inner nuclear membrane (INM) via the INTERNET (integral trafficking from the ER to the nuclear envelope transport) mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…One gradually discovered example of MRIN RTKs, the nuclear EGF receptor (EGFR) family, is involved in multiple cellular functions, including transcriptional regulation, cell proliferation, DNA repair, and chemoand radio-resistance (2)(3)(4)(5)(6)(7)(8)(9)(10). Nuclear EGFR has also been shown to associate with poor prognosis in several cancer types, such as breast cancer, ovarian cancer, and oropharyngeal and esophageal squamous cell carcinomas (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%